2018
DOI: 10.1111/jjns.12243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training and follow‐up calls at home on physical activity and quality of life after a mastectomy

Abstract: Aim To determine the effects of exercise training that was supported with follow‐up calls at home on the postoperative level of physical activity and quality of life of women with breast cancer. Methods The study was carried out with a quasi‐experimental design. Women who had underwent an axillary dissection and mastectomy and who were receiving ongoing chemotherapy treatment in the ambulatory unit of a university hospital were included in the study. Sixty‐two women were randomly assigned to an intervention (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The non-randomised studies lacked complete outcome data due to participant dropout rates and as such the results from these studies are viewed with caution. There were several issues in the included randomised controlled studies worth a mention, 1) several studies 16,18,26,28,[34][35][36][37]40 did not describe the randomisation approach, 2) the primary researcher was in some cases not blinded to the randomisation process 16,18 and 3) in the majority of the randomised studies the outcome assessors were not blinded to the intervention administered. [14][15][16]18,23,24,26,28,31,[34][35][36][37][38]40…”
Section: Quality Appraisal Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The non-randomised studies lacked complete outcome data due to participant dropout rates and as such the results from these studies are viewed with caution. There were several issues in the included randomised controlled studies worth a mention, 1) several studies 16,18,26,28,[34][35][36][37]40 did not describe the randomisation approach, 2) the primary researcher was in some cases not blinded to the randomisation process 16,18 and 3) in the majority of the randomised studies the outcome assessors were not blinded to the intervention administered. [14][15][16]18,23,24,26,28,31,[34][35][36][37][38]40…”
Section: Quality Appraisal Resultsmentioning
confidence: 99%
“…Breast cancer represented 62% of studies. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The participants varied by tumour stage and treatment modality across all studies. The mean age of the study participants was 54 years.…”
Section: Characteristics Of the Study Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“… 80 However some studies have already demonstrated its’ feasibility 75 , 82 and effectiveness in improving physical 75 , 82 , 83 and psychosocial outcomes within cancer survivors. 75 , 82 , 83 , 84 Currently the primary modes of Telehealth delivery have been via mobile applications 85 , web-based platforms 83 , 84 , telephone 75 , 82 , or short messaging service (SMS). 86 To date, there is limited research exploring exercise interventions delivered via live video conferencing platforms such as Zoom, Skype, Microsoft Teams, WhatsApp or Facetime.…”
Section: Telehealth Exercise Interventionsmentioning
confidence: 99%